Computer Assisted Instruction Media: Impact to Students Digital Literacy and Learning Outcomes - Gunawan, Arvidhea Safira; Dewi, Pramesti; Mustikaningtyas, Dewi (Unnes Science Education Journal, 2024)
This study aims to determine the impact of utilization Computer Assisted Instruction (CAI) based learning media in improving digital literacy skills and student learning outcomes. In this study, data collection used observation sheets to improve students' digital literacy skills through observations of experimental and control groupes. It is known that the score of students' digital literacy skills is 81% in the experimental group, while the control group is 67%, meaning that the criteria for students' digital literacy skills in the experimental group are classified as better.  In collecting data to determine the effect of media on student learning outcomes, the Pretest Posttest control group design method is used with a pretest, treatment, and posttest pattern. In practice, 2 groupes are needed as experimental groupes with treatment and control groupes without treatment, and observations are made of students' digital literacy skills during learning activities. From the results of the analysis of student pretests and posttests, it is known that there is an increase in scores in the experimental group as indicated by the average N-Gain value of 57.54%, thus the use of CAI-based learning media is interpreted in the category quite effective in improving student learning outcomes. Then based on the results of the one-way anova analysis for the relationship between the improvement of learning outcomes with digital literacy skills in experimental and control groupes, it is known that the significance value is 0.00 <0.05, as well as the results of the post-hoc test with the Turkey method which shows the significance value between digital literacy and learning outcomes is less than 0.05, which means that the use of CAI-based learning media has an influence on digital literacy as well as student learning outcomes. So it can be concluded that the use of CAI-based media has an impact in improving digital literacy skills and student learning outcomes.